A large handaxe from Wadi Dabsa and early hominin adaptations within the Arabian Peninsula. (6th December 2017) - Foulds, Frederick W.F.; Shuttleworth, Andrew; Sinclair, Anthony; Alsharekh, Abdullah M.; Al Ghamdi, Saud; Inglis, Robyn H.; Bailey, Geoff N.
Abstract: Abstract : The role played by the Arabian Peninsula in hominin dispersals out of Africa has long been debated. The DISPERSE Project has focused on south-western Arabia as a possible centre of hominin settlement and a primary stepping-stone for such dispersals. This work has led to the recent discovery, at Wadi Dabsa, of an exceptional assemblage of over 1000 lithic artefacts, including the first known giant handaxe from the Arabian Peninsula. The site and its associated artefacts provide important new evidence for hominin dispersals out of Africa, and give further insight into the giant handaxe phenomenon present within the Acheulean stone tool industry.